Otosyphilis In An HIV-Infected Patient: The First Case in Vietnam - Pham Phuoc Hung Lam; Tam Thanh Nguyen; Nguyen Ngoc Hieu (Medsci Publications, 2023)
Syphilis has been re-emerging around the world, especially in MSM and people living with HIV. Because of the high number of infections, complications of the disease that were previously rare, now appear again. Otosyphilis is one of them. We reported a case of a 31-year-old MSM patient, HIV-positive, with sudden hearing loss of both ears and tinnitus due to syphilis. This is the first case of otosyphilis detected in Vietnam. The diagnosis of otosyphilis may be delayed because its symptoms are similar to those of other diseases. Therefore, there should be a highly suspected indicator of otosyphilis that can help clinicians orient the diagnosis and handle it in a timely manner.